Microstructural and Mechanical Characteristics of Pure-Cu/brass Dissimilar Joints Welded by Friction Stir Welding Using Various Process Parameters. (2nd September 2022) - C, Ramesh; Tharwan, Mohammed; Kumar, P. Manoj; Gebreyohannes, Dawit Tafesse
Abstract : FSW (friction stir welding) is a solid-state joining method that attracts interest from all industries. The influence of various tool rotational speeds on the microstructure and mechanical characteristics of dissimilar pure Cu-brass joints has been investigated. The travel speed and vertical load were kept constant in the welding trials, at 40 mm/min and 10 kN, respectively, while the tool rotational speed varied from 1000 to 1400 rpm. The increase of the rotational speed to 1400 rpm resulted in degradation of the mechanical properties. The stir zone grain structure was refined; however, the grain size was irregular. Grain refining occurs due to a continuous and discontinuous dynamic recrystallization mechanism. In the grain interior, there were many large dislocations, identifying that incomplete recrystallization took part within the SZ. Instead, the lower rotational speed, i.e., 1000 rpm, led to more uniform grain refinement in the SZ. Moreover, in contrast to the welded zone where very fine grains exist, the base metal and thermomechanically heat-affected zone display coarser grains. Because of the microstructural modification, the stir zone's mechanical characteristics were higher than the base materials, and the mechanical strength and plasticity were simultaneously upgraded. These results indicate that the size of the grains is independent of rotational speed. And mechanical properties like hardness and impact strength decreased as the rotational speed increased.